Evaluation of the McMaster Family Health Team: results and practical implications for quality improvement. Issue 4 (26th November 2018) - Nasser, Laila; Stosic, Alix; Price, David
Abstract : Purpose: To evaluate the McMaster Family Health Team (MFHT) as part of a Continuous Quality Improvement initiative using a set of provincial performance metrics to demonstrate which measures of assessment are actually clinically meaningful in context and where system-level changes might be implemented to improve operational practice. Methods: Measures were selected from the Primary Care Performance Measurement Framework based on data availability for the MFHT and provincial comparators. The measures explored in this paper are those that were deemed to have actionable properties. Data were extracted from billing reports, electronic medical records and information collated for the Association of Family Health Teams of Ontario Data to Decisions database. Metrics were then examined to demonstrate the importance of interpretation in clinical context. Conclusions: Quantitative assessment of performance based on standardised measures is a suitable starting point when evaluating a practice, however it is not appropriate as a stand-alone report card of practice performance. Rather, quantitative measures must be of clinical relevance and applicable to the patient populations of interest in order to create conversation and impact change. Thus, the focus of quality improvement should not be to improve numbers relating to efficiency, patient satisfaction and continuity of care, but rather to determine what drives those numbers and how changes might be made at a system or practice level that will optimise clinician buy-in.